Clinical and Laboratory Findings of Plasmodium Vivax Malaria in Colombia, 2001 (2003)
ABSTRACT: A descriptive study was carried out in 104 patients with Plasmodium vivax malaria, from the region of Turbo (Antioquia, Colombia). Clinical features and levels of hemoglobin, glycemia, serum bilirubin, alanine-aminotransferase (ALT), aspartate-aminotransferase (AST), creatinine and complete blood cell profile were established. 65% of the studied individuals were men and their mean age was 23. Of all individuals 59% had lived in the region for > 1 year and 91% were resident in the rural area. 42% were farmers and 35% had a history of malaria. The mean parasitaemia was 5865 parasites/mm³. The evolution of the disease was short (average of 4.0 days). Fever, headache and chills were observed simultaneously in 91% of the cases while the most frequent signs were palmar pallor (46%), jaundice (15%), hepatomegaly (17%), and spleen enlargement (12%). Anemia was found in 39% of the women and in 51% of the men, 8% of individuals had thrombocytopaenia and 41% had hypoglycemia.